15N tracing reveals preference for different nitrogen forms of Fusarium oxysporum f. sp. cubense tropical race 4 - He, Chen; Jia, Zhongjun; Fan, Pingshan; Ruan, Yunze; Liang, Ye; Ma, Jingjing; Li, Jinku (Frontiers in Microbiology, 2023)
Soil acidification is often associated with plant uptake of ammonium and elevated incidence of Fusarium wilt of banana, a disease caused by the soil-borne fungus Fusarium oxysporum f. sp. cubense (Foc TR4). However, the nitrogen metabolic preferences of Fusarium oxysporum pathogens remain unknown. In this study, we investigated the ecophysiological patterns of Foc TR4 grown on different combinations of organic and inorganic nitrogen. Potato Dextrose Agar (PDA) and Rose Bengal Medium (RBM) were used as an organic nitrogen source, which was sequentially replaced with inorganic N (0%, 50% or 90%) in the form 15NH4NO3 or NH415NO3 to reveal preferential assimilation of ammonium or nitrate. Mycelium biomass and nitrogen content decreased significantly, while the carbon content and C:N ratio increased in Foc TR4 grown on media containing inorganic nitrogen sources. Mycelium biomass was negatively correlated with C:N ratio. Mycelium 15N abundance increased significantly between the PDA50+A50/RBM50+A50 treatments (50% organic nitrogen+50%15NH4NO3) and the PDA10+A90/RBM10+A90 treatments (10% organic nitrogen+90%15NH4NO3). These results indicate that the higher C:N ratio reduced mycelium growth by reducing its biomass and diameter and showed that Foc TR4 preferred to use ammonium nitrogen to promote the growth. These findings suggest that treating banana crops with a combination of organic and inorganic (i.e., nitrate) nitrogen could be a better way to defend against Fusarium wilt of banana.